(untitled) (Orinoquia, 2023)
The Chikungunya virus (CHIKV) is a single-stranded positive-sense RNA virus that belongs to the Alphavirus genus of the Togaviridae family. It is primarily transmitted by Aedes aegypti and albopictus mosquitoes. Its genome encodes four non-structural proteins (NSP 1-4) and three structural proteins (C, E1, and E2). Four lineages of this virus have been identified, namely the West African, East African, Central and South African (ECSA), Asian (AL), and Indian Ocean Lineages (IOL). CHIKV is an endemic arbovirus circulating in 51 countries in the Americas. Clinical manifestations attributed to it include high fever, rash, myalgia, and episodes of arthralgia, which subsequently lead to chronic pain and disability, especially in the joints. Sequencing the complete genome of the Chikungunya virus is essential to understand its biology, evolution, and spread and to develop effective strategies for prevention, diagnosis, and treatment. This information is crucial for combating the disease and minimizing its impact on public health. For these reasons, the complete genome of the Chikungunya virus strain br33, identified in the northeastern city of Recife, in the state of Pernambuco, Brazil, was sequenced. The genome has a size of 11,601 nucleotides and contains coding regions for two polyproteins. A phylogenetic analysis indicates that the recent Brazilian strain of CHIKV belongs to the East, Central, and South African lineage (ECSA). This phylogenetic identification is important because this particular genotype has been associated with greater damage and clinical severity. Until 2016, the CHIKV virus was directly associated with travel, and its transmission was limited. Subsequently, the largest outbreak occurred in the state associated with the introduction of a new ECSA lineage, as identified in this study. It is highly likely that new CHIKV outbreaks will occur in the near future due to the abundance of competent vectors in Brazil and a susceptible population, exposing more than 11 million inhabitants to an increasing risk of infection.